Pengaruh Ajaran Tri Pantangan, Sikap, dan Pemberian Reward terhadap Niat Melakukan Whistleblowing - Susanto, Aurelia; Yulita Setiawanta; Enny Susilowati Mardjono; Hermawan Triono (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to see whether there is an influence of the Tri Pantangan teachings, attitudes, and provision of rewards on the intention to do whistleblowing. The population in this study were accounting students at Dian Nuswantoro University Semarang. The sample was taken using puposive sampling technique, with 101 students selected as research respondents. Data were collected through questionnaires as a data collection method. To analyze the data, this study used multiple linear regression analysis assisted by SPSS 25. The results showed that the tri abstinence teachings and attitudes affect the intention of whistleblowing, while the provision of rewards showed no effect on the intention of whistleblowing.